Coronary angiogriphy in left ventricular dysfunction patients with no clinical evidence of ischemic heart disease - taj al deen, Wisam , s.; farhan, Hassan Ali; al zaidi, mahhdu s. (AL-Kindy College Medical Journal, 2013)
Background : Coronary artery disease is theunderlying cause in approximately two thirds of patients with systolic heart failure ; Coronary artery angiogriphy may be useful to define the presence , Anatomical characteristics ,and functional significance of Coronary artery disease in selected heart failure patients with or without signs and aymptoms of Coronary artery disease. Objectives: to verify the clinical usefulness of coronary angiography (CA) in congestive heart failure (CHF) patients with no history of ischemic heart disease and to identify predictive factors for performing coronary angiography to patients with congestive heart failure with no obvious ischemia. Methods :this is a cross-sestional study conducted Ibn al –Bitar center for cardiac surgery during a period between November 2009 and November 2010 ;all included patients have symptomatic LV dyfunctional with NYHA functional class II or more with no clinical evidence of IHD .History, physical examination had been performed for each patient , in addition ti blood tests ,ECG ,CXR, echocardiography and Coronary angiogriphy Results :Among 112 patients with symptomatic LV dysfunction of unknown cause enrolled in this study male :female ratio 3:1 their age (17 -77 years )there were 14 patients (12.5%)with significant Coronary artery disease , statistical analysis between CADand non CAD group show :the CAD were more common in male 11 patients (78% ) smokers(1)Were female , 25 patients (22.3%) were diabetic , 25 diabetic (22.3%) were hypertensive ,50 diabetic (44.6%) were smokers . 4 diabetic3.5) with family history of dilatedhyperlipidemia and 3 diabetic (2.6%) ) with family history ischemic heart disease (IHD in close relative at age <50 years in men and <55 years in women ) as demographic distribution of patients in table 1 .coronary angiography show that are 14 patients (12.5%) with significant coronary artery disease (CAD) and 98 patients (87.5%) with significant coronary artery disease . as shown in figure 1 . eleven patients (78%) of patients (22%) were female statistical analysis shows that the male is more predominant in CAD groups as shown in table 2 . twelve patients (85.7%) of patients with CAD were smokers while only 38 patients (38.7%) were smokers in non CAD group . statistical analysis shows there is significant difference between the two groups ( p value < 0.01 ) as shown in table 3 .nine patients (64.2%) of patients with CAD were diabetics while 16 patients (16.3%)were diabetics in non CAD group , statistical analysis shows there is significant difference between the two groups (p value < 0.005) as shown in table (3) .there is no statistical between the mean of left ventricular ejection fraction of CAD group ( 37 ±10 %) and that of non CAD (36±9 % ) , p value > 0.5 as shown in table 6 . figure 2 revealed that LAD lesion was most common coronary artery lesion which represent 12 (85%) followed by in order of frequency LCX 42 % ,RCA 28% and LMS 7% ; in addition to that 57% with single vessel disease ,14.2% with 2 vessel disease and 28.4%with r vessel disease (2)Leads , ST depression ≥1 mm or deep T wave inversion had been excluded (